Baronica Maria Wambolt in zdravljenje ljudi na Dolenjskem s pomočjo homeopatije - Židov, Nena (Etnolog. Nova vrsta (Ljubljana), 2007)
Baroness Maria Wambolt lived at Hmeljnik Castle near Novo Mesto from 1876 to 1915. She treated people and pigs as a lay homeopath at the turn of the century. Archive material on her treatment of people has been preserved, in particular a notebook with data on her patients from the early 20th century. She mainly treated the peasant population of all ages from Dolenjska, who turned to her for help with chronic and acute health problems.
Keywords: Slovenci; Slovenes; zdravilstvo; zdravje; ljudska medicina; laična homeopatija; history; zgodovina; plemstvo; grad Hmeljnik